Affective, Psychomotoric, and Cognitive Changes in Young Women at Wachid Hasyim Tebuireng High School are BSE with Blended Learning by Health Education - Nurullita Widyazizah; Yenny Puspitasari; Agustin Widyowati (Journal Of Nursing Practice, 2024)
Background: Breast cancer is a significant health concern among Indonesian women, emphasizing the need for effective prevention strategies. Purpose: This study investigates the effects of health education utilizing the Breast Self-Examination (BSE) method, augmented with blended learning, on the affective, psychomotor, and cognitive aspects of young women attending Wachid Hasyim Tebuireng High School. Method: Employing a Pre-Test Post-Test Control Group design, participants were divided into control and intervention groups. The intervention group received health education utilizing the BSE technique combined with blended learning, while the control group did not undergo this intervention. Results: Results indicated substantial improvements in the affective, psychomotor, and cognitive domains among young women who received health education with blended learning. Positive attitudes towards BSE increased significantly, with average scores rising from 75.1 to 85.3 post-intervention. Similarly, psychomotor skills improved, evidenced by scores escalating from 72.4 to 84.5 after receiving education. Moreover, cognitive understanding saw a remarkable enhancement, with average scores soaring from 67.3 to 87.6 following the intervention. Conclusion: The study concludes that integrating blended learning with health education significantly enhances young women's psychomotor, affective, and cognitive responses to BSE. These findings underscore the efficacy of blended learning in augmenting the impact of health education, particularly in empowering young women with essential knowledge and skills for breast cancer prevention and early detection.